How Entrepreneurial Learning Drives E-Intention via Creative Confidence, and the Boundary Condition of Digital Competence in Pakistan - Madiha Hamid (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This study primarily aimed to investigate the digital research competencies of business students based on respondents’ self-reported creativity level in developing new research projects and their overall entrepreneurial intention. The secondary purpose was two-fold: first, to determine whether the use of different emerging technologies has a significant effect on students’ digital skills within a research context; and second, to clarify the ranking of these emerging technologies or their various combinations, which most impact or predict students’ digital competencies. Methodology: Based on convenience sampling technique, the data were gathered from 357 business students attending universities in Pakistan in an effort to recruit students who had taken, or were currently taking, an entrepreneurship course at their respective business school. The design of the study sought to ensure that students had exposure to formal entrepreneurial learning. The study collected data in two stages, the first with a pilot study and the second profile of business students. Findings: The study highlights that entrepreneurial learning has significant impact on e-entrepreneurial intention among business students in Pakistan, as well as mediating moderating effects of self-perceived creativity and digital competences impact on e-entrepreneurial intention. Implications/Novel Contribution: The study uniquely, suggests that the motivational force of creative conviction is greatly intensified when combined with the requisite technical capabilities to realize digital innovations. These findings highlight the need for a contextualized intention model, which is to say that new e-entrepreneurs cannot emerge from the digital economy without both creative self-efficacy and domain-specific digital capabilities enhanced through systematic entrepreneurial education. The study brings key policy insights for scholars and practitioners in the field.